An Unusual Presentation of Clear Cell Odontogenic Carcinoma: Case Report - Velazque DDS, MSc, Lida; Claudio DDS, MSc, PhD, Carlos; Pfuro, Roger (Odovtos - International Journal of Dental Sciences, 2016)
Clear cell odontogenic carcinoma (CCOC) is a uncommon aggressive neoplasm of variable performance, which is primarily located in the mandibular anterior region, to a lesser extent in the maxilla, with prevalence in women between the fifth and seventh decades of life. Histologically it is constituted by networks of cells with clear cytoplasm mixed with cells containing eosinophilic cytoplasm rich in glycogen, surrounded by bands of collagen, you can make the local or distant metastases, highly recurrent, so it should include long-term follow-up patient and differentiated from other conditions with clear cell. The case of a male patient aged 52, with a mixed injury unusual presentation covering maxilla, zygomatic, orbital and right nasal cavity, without involvement of regional lymph nodes, no apparent metastases is reported.